The integration of the epistemologies of science and Islam in the development of a curriculum system for modern Islamic boarding schools in Indonesia - Iyus Herdiana Saputra; Tobroni Tobroni; Moh Nurhakim; Diah Karmiyati (Bulletin of Educational Management and Innovation, 2026)
Background: The dichotomy between religious studies and science remains a major issue in the Islamic education system, particularly in modern Islamic boarding schools, necessitating an epistemological integration model capable of uniting revelation, reason, and empiricism within a single scientific framework. Purpose: This study aims to analyze the epistemological integration of science and Islam in the development of the curriculum system for modern Islamic boarding schools in Indonesia, using a case study of Trensains Muhammadiyah Sragen. Method: This study employs a qualitative approach with an intrinsic case study design. Data were collected through in-depth interviews, participant observation, and document analysis, and were subsequently analyzed using the Miles, Huberman, and Saldaña interactive model. Findings: The results indicate that epistemological integration is substantively achieved through the reconstruction of the relationship between revelation, reason, and empiricism within the framework of tawhid. This integration is manifested in an integrated curriculum as well as learning practices based on ayat kauniyah, inquiry-based learning, and scientific research by students. The findings also indicate that this integration contributes to the development of students’ holistic competencies, encompassing critical thinking skills, scientific understanding, and spiritual awareness. However, implementation still faces challenges regarding teacher competencies and the availability of integrative teaching materials. The novelty of this study lies in the formulation of an operational epistemological integration model within the curriculum system and pedagogical practices of modern Islamic boarding schools.